2018
DOI: 10.1002/fld.4696
|View full text |Cite
|
Sign up to set email alerts
|

High‐order ghost‐point immersed boundary method for viscous compressible flows based on summation‐by‐parts operators

Abstract: Summary A high‐order immersed boundary method is devised for the compressible Navier‐Stokes equations by employing high‐order summation‐by‐parts difference operators. The immersed boundaries are treated as sharp interfaces by enforcing the solid wall boundary conditions via flow variables at ghost points. Two different interpolation schemes are tested to compute values at the ghost points and a hybrid treatment is used. The first method provides the bilinearly interpolated flow variables at the image points of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The ghost point immersed boundary method (IBM) by [6], [7], [8] is employed. In this method, the fluid domain is discretized on a Cartesian grid.…”
Section: Ghost Point Immersed Boundary Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ghost point immersed boundary method (IBM) by [6], [7], [8] is employed. In this method, the fluid domain is discretized on a Cartesian grid.…”
Section: Ghost Point Immersed Boundary Methodsmentioning
confidence: 99%
“…The nondimensional viscous perturbation flux vectors F v and G v are defined similarly as in the standard formulation of the compressible Navier-Stokes equations, cf. [7], [8]. A Newtonian fluid with the Sutherland law for the viscosity, a perfect gas with the ratio γ = 1.4 of specific heats for air, and a constant Prandtl number P r = 0.72 are considered.…”
Section: Governing Equations 21 Compressible Navier-stokes Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a few studies on the acoustic scattering (Seo and Mittal, 2011;Bae and Moon, 2012;Sun et al, 2012). However, there has been no DNS of the aeroacoustic sound by the immersed boundary method of discrete approach except that Khalili et al (2019) showed limited results on the aeroacoustic sound generated from a flow past a circular cylinder. In order to capture acoustic waves of small amplitude the accuracy of the immersed boundary method should be checked carefully since it can be lost by interpolation, treatment of boundary conditions, or other reasons.…”
Section: Introductionmentioning
confidence: 99%